Genetic Structure and Evolutionary History of Three Alpine Sclerophyllous Oaks in East Himalaya-Hengduan Mountains and Adjacent Regions - Feng, Li; Zheng, Qi-Jian; Qian, Zeng-Qiang; Yang, Jia; Zhang, Yan-Ping; Li, Zhong-Hu; Zhao, Gui-Fang (Frontiers in Plant Science, 2016)
The East Himalaya-Hengduan Mountains (EH-HM) region has a high biodiversity and harbours numerous endemic alpine plants. This is probably the result of combined orographic and climate oscillations occurring since late Tertiary. Here, we determined the genetic structure and evolutionary history of alpine oak species (including Q. spinosa, Q. aquifolioides and Q. rehderiana) using both cytoplasmic-nuclear markers and ecological niche models (ENMs), and elucidated the impacts of climate oscillations and environmental heterogeneity on their population demography. Our results indicate there were mixed genetic structure and asymmetric contemporary gene flow within them. The ENMs revealed a similar demographic history for the three species expanded their ranges from the last interglacial (LIG) to the last glacial maximum (LGM), which was consistent with effective population sizes changes. Effects of genetic drift and fragmentation of habitats were responsible for the high differentiation and the lack of phylogeographic structure. Our results support that geological and climatic factors since Miocene triggered the differentiation, evolutionary origin and range shifts of the three oak species in the studied area and also emphasize that a multidisciplinary approach combining molecular markers, ENMs and population genetics can yield deep insights into diversification and evolutionary dynamics of species.